Nanofiltration membrane preparation method for regulating interfacial polymerization reaction by utilizing carbon nitride photogenerated charge

Through the interfacial polymerization reaction of carbon nitride photogenerating charge regulation, a high-permeability nanofiltration membrane was prepared, which solved the problem of checks and balances between water flux and retention rates of traditional nanofiltration membranes, and achieved significant improvement in water flux and high efficiency of divalent ion retention.

CN119733384AActive Publication Date: 2025-04-01TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411651163.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-01
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The water flux and retention rate of traditional nanofiltration membranes are checked and balanced, making it difficult to improve separation performance and separation efficiency at the same time.

Method used

By utilizing the carbon nitride photogenerating charge regulation interface polymerization reaction, a high permeability nanofiltration membrane with an ultra-thin polyamide separation layer was prepared. This method performs interfacial polymerization under light, and uses the photoelectrochemical characteristics of carbon nitride to regulate the interfacial polymerization rate.

Benefits of technology

The water flux of the nanofiltration membrane is increased by more than 3 times, while maintaining a high retention rate of divalent ions in the water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005140964810000011
    Figure HDA0005140964810000011
  • Figure HDA0005140964810000012
    Figure HDA0005140964810000012
  • Figure HDA0005140964810000021
    Figure HDA0005140964810000021
Patent Text Reader

Abstract

The invention provides a preparation method of a nanofiltration membrane for regulating and controlling interfacial polymerization reaction by utilizing carbon nitride photogenerated charge, and belongs to the technical field of water treatment membranes. The preparation method comprises the following steps: (1) adding carbon nitride film-making sol into an aqueous solution of a polyamine monomer, and carrying out ultrasonic dispersion to obtain a mixed dispersion liquid; (2) preparing an organic phase monomer solution; (3) adding an ultrafiltration support base membrane into the mixed dispersion liquid, infiltrating, then taking out, adding into the organic phase monomer solution, and carrying out interfacial polymerization reaction to obtain a high-permeability membrane containing an ultrathin polyamide separation layer; wherein the infiltration and the interfacial polymerization reaction are carried out under illumination; and (4) carrying out heat treatment on the high-permeability membrane containing the ultrathin polyamide separation layer to obtain the nanofiltration membrane. According to the preparation method disclosed by the invention, the photoelectrochemical characteristics of carbon nitride are utilized, and electrostatic repulsion exists between positive charges on the surface of carbon nitride and piperazine molecules under illumination, so that the interfacial polymerization rate is regulated and controlled, and the high-permeability nanofiltration membrane with an ultrathin polyamide separation layer is further prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment membranes, and in particular relates to a method for preparing a nanofiltration membrane by regulating an interfacial polymerization reaction using photogenerated charges of carbon nitride. Background Art

[0002] Membrane separation has the characteristics of low energy consumption and high separation efficiency. It is an ideal means to remove pollutants and purify water. As a typical low-pressure separation membrane, nanofiltration membrane (TFC) based on thin layer composite has become the preferred solution for deep purification of drinking water and industrial wastewater treatment. However, the separation performance of traditional nanofiltration membrane represented by polyamide is restricted by the balance between water flux and retention rate. Exploring effective methods to improve the separation performance of polyamide nanofiltration membrane has become a hot spot in nanofiltration technology research.

[0003] In the traditional nanofiltration membrane interfacial polymerization process, the polyamine monomer piperazine molecules diffuse from the aqueous phase to the organic phase and undergo a violent polycondensation reaction with the organic phase monomer trimethylol chloride. This rapid reaction kinetic process induces local polymerization on the interface, and it is very easy to form a dense and uneven membrane layer structure as the diffusion progresses along the thickness, which greatly restricts the water permeability of the formed polyamide nanofiltration membrane. At present, most studies use the method of adding nanomaterials to the membrane-making monomer solution, and the construction of a hydrophilic interface has improved the water flux of the nanofiltration membrane to a certain extent. Nevertheless, since the introduction of heterogeneous materials can easily cause the formation of composite interface defects, the low amount of nanomaterials added has limited improvement in membrane separation performance. Exploring more precise control methods for polymer membrane structure has become the key to obtaining selective layer materials with high water flux, good monovalent and polyvalent selectivity, and strong anti-pollution ability.

[0004] Carbon nitride nanosheets, due to their graphene-like two-dimensional layered structure, are ideal materials for selective permeation and separation at the sub-nanometer scale. Usually, researchers prepare carbon nitride-modified separation membranes by compounding the exfoliated carbon nitride into a polymer matrix, mainly by leveraging the intrinsic pores and hydrophilic sites on its two-dimensional plane to improve the performance of nanofiltration membranes. As a new type of photosensitive semiconductor material, the application of the photoactive properties of carbon nitride in nanofiltration membranes has only been disclosed for in-situ degradation of separated organic pollutants, and its potential for photogenerated charges to enhance membrane separation performance remains to be explored. Summary of the invention

[0005] Based on this, the present invention proposes a method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride to solve the above technical problems.

[0006] The present invention provides a method for preparing a nanofiltration membrane by regulating an interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0007] (1) subjecting a nitrogen-containing precursor to thermal polymerization to obtain a bulk carbonitride compound, treating the bulk carbonitride compound in an acid solution to obtain a carbon nitride film-forming sol; adding the obtained carbon nitride film-forming sol to an aqueous solution of a polyamine monomer, and performing ultrasonic dispersion to obtain a mixed dispersion;

[0008] (2) dissolving the organic phase monomer in an organic solvent and stirring to obtain an organic phase monomer solution;

[0009] (3) adding the ultrafiltration support base membrane to the above-mentioned mixed dispersion to wet it, and then taking it out and adding it to the above-mentioned organic phase monomer solution to carry out interfacial polymerization reaction to obtain a high permeability membrane containing an ultrathin polyamide separation layer; wherein the wetting and interfacial polymerization reaction are both carried out under light;

[0010] (4) After heat treatment of the high permeability membrane containing the ultra-thin polyamide separation layer, a nanofiltration membrane regulated by photogenerated positive charges of carbon nitride is obtained.

[0011] Furthermore, in step (1), the nitrogen-containing precursor includes at least one of cyanamide, dicyandiamide, melamine, urea and thiourea.

[0012] Furthermore, in step (1), the ratio of the bulk carbon nitrogen compound to the acid solution is 1 g: 10 to 50 mL;

[0013] In step (1), the concentration of the obtained carbon nitride film-forming sol is 1.0 to 2.0 mg / ml;

[0014] In step (1), the concentration of carbon nitride in the aqueous solution of the polyamine monomer is 0.1 to 2.0 mg / mL.

[0015] Furthermore, in step (1), the polyamine monomer includes at least one of piperazine and its derivatives, o-phenylenediamine and its derivatives, m-phenylenediamine and its derivatives, diethylenetriamine, triethylenetetramine, polyethyleneimine, and the like.

[0016] Furthermore, in step (2), the organic phase monomer includes at least one of isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, cycloalkane polyacyl chloride, and polysulfonyl chloride;

[0017] In step (2), the concentration of the organic phase monomer in the organic solvent is 0.5 to 3 mg / mL.

[0018] Furthermore, in step (3), the illumination is provided by a xenon lamp; the intensity of the illumination is 100 to 300 mw / cm 2 .

[0019] Furthermore, in step (3), the soaking time is 30 to 180 seconds.

[0020] Furthermore, in step (3), the time of the interfacial polymerization reaction is 15 to 120 seconds, the temperature of the interfacial polymerization reaction is 20 to 30° C., and the humidity of the interfacial polymerization reaction is 45 to 70%.

[0021] Furthermore, in step (4), the heat treatment temperature is 40 to 70° C. and the heat treatment time is 10 to 60 minutes.

[0022] The present invention also provides a nanofiltration membrane prepared by any of the above-mentioned nanofiltration membrane preparation methods using carbon nitride photogenerated charges to regulate interfacial polymerization reactions.

[0023] The present invention has the following advantages:

[0024] The present invention utilizes the photoelectrochemical properties of carbon nitride. The positive charge on the surface of carbon nitride under light has an electrostatic repulsion with piperazine molecules, thereby regulating the interfacial polymerization rate, and then preparing a high-permeability nanofiltration membrane with an ultra-thin polyamide separation layer. The permeation flux of the obtained nanofiltration membrane is more than 3 times higher than that of the polyamide membrane without carbon nitride added, and the divalent ions in water are intercepted. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 This is a transmission electron microscope photograph of the carbon nitride nanowires in Example 1 of the present invention.

[0027] Figure 2 Schematic diagram of pure water flux of Examples 1 to 4 of the present invention and Comparative Examples 1 to 4.

[0028] Figure 3 Schematic diagram of the brine flux and retention stability of sodium sulfate solution in Example 4 of the present invention.

[0029] Figure 4 It is a schematic diagram of the brine flux and retention stability of sodium sulfate solution in comparative application example 2 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0031] On the one hand, an embodiment of the present invention provides a method for preparing a nanofiltration membrane by regulating an interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0032] (1) subjecting a nitrogen-containing precursor to thermal polymerization to obtain a bulk carbonitride compound, treating the bulk carbonitride compound in an acid solution to obtain a carbon nitride film-forming sol; adding the obtained carbon nitride film-forming sol to an aqueous solution of a polyamine monomer, and performing ultrasonic dispersion to obtain a mixed dispersion;

[0033] (2) dissolving the organic phase monomer in an organic solvent and stirring to obtain an organic phase monomer solution;

[0034] (3) adding the ultrafiltration support base membrane to the above-mentioned mixed dispersion to wet it, and then taking it out and adding it to the above-mentioned organic phase monomer solution to carry out interfacial polymerization reaction to obtain a high permeability membrane containing an ultrathin polyamide separation layer; wherein the wetting and interfacial polymerization reaction are both carried out under light;

[0035] (4) After heat treatment of the high permeability membrane containing the ultra-thin polyamide separation layer, a nanofiltration membrane regulated by photogenerated positive charges of carbon nitride is obtained.

[0036] The method for preparing a nanofiltration membrane by utilizing photogenerated charges of carbon nitride to regulate interfacial polymerization reactions proposed in an embodiment of the present invention utilizes the photoelectrochemical properties of hydrophilic carbon nitride. The positively charged interface formed under light produces electrostatic repulsion with positively charged polyamine monomers, thereby regulating the diffusion rate of aqueous phase monomers and further regulating the rate of interfacial polymerization reactions, thereby obtaining a lower separation layer thickness and a controllable hydrophilic surface, thereby achieving the purpose of increasing water flux.

[0037] In one embodiment of the present invention, in step (1), the nitrogen-containing precursor includes at least one of cyanamide, dicyandiamide, melamine, urea and thiourea.

[0038] In one embodiment of the present invention, in step (1), the thermal polymerization method is specifically: adding a nitrogen-containing precursor into a crucible and placing it in a muffle furnace for high-temperature calcination, and then grinding the calcined product into powder in a mortar to obtain a bulk carbonitride.

[0039] Furthermore, in step (1), the high temperature calcination temperature is 500-600° C., and the high temperature calcination time is 2-6 hours.

[0040] In one embodiment of the present invention, in step (1), the bulk carbon nitrogen compound is placed in an acid solution for treatment, specifically: the bulk carbon nitrogen compound is placed in a beaker containing an acid solution, stirred, and then the acid solution is removed by filtration, and the powder obtained by filtration is washed with deionized water until it is neutral, and then the carbon nitrogen compound after filtration is diluted with deionized water, ultrasonicated, centrifuged, and the supernatant is taken to obtain a carbon nitride film sol.

[0041] Furthermore, the stirring temperature is 50-70°C, the stirring time is 3-8 hours, the ultrasonic time is 1-3 hours, the centrifugal speed is 3000-6000 rpm, and the centrifugal time is 10-50 minutes.

[0042] Preferably, the stirring temperature is 60° C., the stirring time is 5 h, the ultrasonic time is 2 h, the centrifugal speed is 5000 rpm, and the centrifugal time is 20 min.

[0043] Furthermore, in step (1), the acid solution includes at least one of concentrated hydrochloric acid, concentrated sulfuric acid or concentrated nitric acid.

[0044] Furthermore, in step (1), the bulk carbon nitrogen compound and the acid solution are used in a ratio of 1 g: 10 to 50 mL. Preferably, the bulk carbon nitrogen compound and the acid solution are used in a ratio of 1 g: 20 mL.

[0045] In one embodiment of the present invention, in step (1), the concentration of the obtained carbon nitride film-forming sol is 1.0-2.0 mg / ml. In step (1) of the embodiment of the present invention, the carbon nitride exists in the carbon nitride film-forming sol in the form of hydrophilic nanowires.

[0046] In one embodiment of the present invention, in step (1), the concentration of carbon nitride in the aqueous solution of the polyamine monomer is 0.1-2.0 mg / mL. In step (2), the concentration of the aqueous solution of the polyamine monomer is 1-6 mg / mL.

[0047] In one embodiment of the present invention, in step (1), the polyamine monomer includes at least one of piperazine and its derivatives, o-phenylenediamine and its derivatives, m-phenylenediamine and its derivatives, diethylenetriamine, triethylenetetramine, polyethyleneimine, etc. Preferably, the polyamine monomer is piperazine.

[0048] In one embodiment of the present invention, in step (2), the organic phase monomer includes at least one of isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, cycloalkane polyacyl chloride, and polysulfonyl chloride. Preferably, the organic phase monomer is trimesoyl chloride, i.e., 1,3,5-benzenetricarboxylic acid chloride.

[0049] Furthermore, in step (2), the concentration of the organic phase monomer in the organic solvent is 0.5 to 3 mg / mL.

[0050] Furthermore, in step (2), the organic solvent includes at least one of n-hexane, n-octane, n-heptane, dichloromethane, chloroform, carbon tetrachloride, benzene, toluene, xylene, pentane and cyclohexane.

[0051] In one embodiment of the present invention, in step (3), the ultrafiltration support bottom membrane is a polycarbonate filter membrane, a polytetrafluoroethylene filter membrane, a polyethersulfone filter membrane, a polysulfone filter membrane or a polypropylene filter membrane.

[0052] In one embodiment of the present invention, in step (3), the illumination is provided by a xenon lamp. The intensity of the illumination is 100 to 300 mw / cm 2 .

[0053] In one embodiment of the present invention, in step (3), the soaking time is 30 to 180 seconds.

[0054] In one embodiment of the present invention, in step (3), the time of the interfacial polymerization reaction is 15 to 120 seconds, the temperature of the interfacial polymerization reaction is 20 to 30° C., and the humidity of the interfacial polymerization reaction is 45 to 70%.

[0055] Furthermore, step (3) further comprises, after the interfacial polymerization reaction, pouring out excess liquid and washing the treated surface of the ultrafiltration support bottom membrane with an organic solvent to remove unreacted organic phase monomers.

[0056] In one embodiment of the present invention, in step (4), the temperature of the heat treatment is 40 to 70° C. and the time of the heat treatment is 10 to 60 minutes.

[0057] In the embodiment of the present invention, in step (4), the high permeability membrane containing the ultra-thin polyamide separation layer is subjected to heat treatment to achieve further cross-linking. The nanofiltration membrane obtained after the heat treatment can be immersed in water for storage.

[0058] On the other hand, the present invention also proposes a nanofiltration membrane prepared by the above-mentioned method for preparing a nanofiltration membrane by regulating the interfacial polymerization reaction using photogenerated charges of carbon nitride.

[0059] The present invention will be described in detail below with reference to embodiments and the accompanying drawings.

[0060] Embodiment 1:

[0061] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0062] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0063] Step 2: Prepare a 2 mg / mL piperazine aqueous solution, add carbon nitride film-forming sol to make the concentration of carbon nitride in the piperazine aqueous solution 0.5 mg / mL, and disperse it evenly by ultrasound to obtain a mixed dispersion; take 5 ml of the mixed dispersion and add it dropwise to the surface of the polyethersulfone support base film to infiltrate for 120 seconds, and remove the residual liquid on the surface; wherein the infiltration is carried out under light, and the light is formed by xenon lamp irradiation, and the intensity of the light is 100 mw / cm 2 .

[0064] Step 3: Prepare a 2 mg / mL hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the hexane solution containing trimesoyl chloride for interfacial polymerization. After the reaction lasts for 30 seconds, remove the excess liquid, and then soak the resulting membrane in the hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, thereby obtaining a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C and the reaction humidity is 60%. The reaction is carried out under light, which is formed by xenon lamp irradiation, and the intensity of the light is 100 mw / cm 2 .

[0065] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0066] Embodiment 2:

[0067] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0068] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0069] Step 2: Prepare a 4 mg / mL piperazine aqueous solution, add carbon nitride film-forming sol to make the concentration of carbon nitride in the piperazine aqueous solution 0.5 mg / mL, and disperse it evenly by ultrasound to obtain a mixed dispersion; take 5 ml of the mixed dispersion and add it dropwise to the surface of the polyethersulfone support base film to infiltrate for 120 seconds, and remove the residual liquid on the surface; wherein the infiltration is carried out under light, and the light is formed by irradiation with a xenon lamp, and the intensity of the light is 100 mw / cm 2 .

[0070] Step 3: Prepare a 2 mg / mL hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the hexane solution containing trimesoyl chloride for interfacial polymerization. After the reaction lasts for 30 seconds, remove the excess liquid, and then soak the resulting membrane in the hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, thereby obtaining a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C and the reaction humidity is 60%. The reaction is carried out under light, which is formed by xenon lamp irradiation, and the intensity of the light is 100 mw / cm 2 .

[0071] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0072] Embodiment 3:

[0073] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0074] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0075] Step 2: Prepare a 2 mg / mL piperazine aqueous solution, add carbon nitride film-forming sol to make the concentration of carbon nitride in the piperazine aqueous solution 1.0 mg / mL, and disperse it evenly by ultrasound to obtain a mixed dispersion; take 5 ml of the mixed dispersion and add it dropwise to the surface of the polyethersulfone support base film to infiltrate for 120 seconds, and remove the residual liquid on the surface, wherein the infiltration is carried out under light, and the light is formed by irradiation with a xenon lamp, and the intensity of the light is 100 mw / cm 2 .

[0076] Step 3: Prepare a 2 mg / mL n-hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the n-hexane solution containing trimesoyl chloride for interfacial polymerization reaction. After the reaction lasts for 30 seconds, remove the excess liquid. Then, soak the obtained membrane in the n-hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, and obtain a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C, the reaction humidity is 60%, and the reaction is carried out under light, the light is formed by xenon lamp irradiation, and the intensity of the light is 100mw / cm 2 .

[0077] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0078] Embodiment 4:

[0079] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0080] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0081] Step 2: Prepare a 4 mg / mL piperazine aqueous solution, add carbon nitride film-forming sol to make the concentration of carbon nitride in the piperazine aqueous solution 1.0 mg / mL, and disperse it evenly by ultrasound to obtain a mixed dispersion; take 5 ml of the mixed dispersion and add it dropwise to the surface of the polyethersulfone support base film to infiltrate for 120 seconds, and remove the residual liquid on the surface, wherein the infiltration is carried out under light, and the light is formed by irradiation with a xenon lamp, and the intensity of the light is 100 mw / cm 2 .

[0082] Step 3: Prepare a 2 mg / mL n-hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the n-hexane solution containing trimesoyl chloride for interfacial polymerization reaction. After the reaction lasts for 30 seconds, remove the excess liquid. Then, soak the obtained membrane in the n-hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, and obtain a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C, the reaction humidity is 60%, and the reaction is carried out under light, the light is formed by xenon lamp irradiation, and the intensity of the light is 100mw / cm2 .

[0083] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0084] Comparative Example 1:

[0085] A method for preparing a conventional polyamide microfiltration membrane (no carbon nitride is added to the aqueous monomer solution, and the wetting and interfacial polymerization reactions are not carried out under light), comprising the following steps:

[0086] Step 1: Take piperazine as the aqueous phase monomer and trimesoyl chloride as the organic phase monomer, dissolve them in water and n-hexane respectively, and prepare a piperazine solution with a concentration of 4.0 mg / mL and a trimesoyl chloride n-hexane solution with a concentration of 2 mg / mL respectively.

[0087] Step 2: Using polyethersulfone ultrafiltration membrane as the supporting base membrane and piperazine solution as the aqueous phase monomer, take 5 ml of the solution and drop it onto the surface of the polyethersulfone supporting base membrane for aqueous phase infiltration. After standing for 120 seconds, take out the polyethersulfone filter membrane and remove the surface liquid.

[0088] Step 3: Immerse the surface of the ultrafiltration membrane in step (3) in a n-hexane solution of trimesoyl chloride to carry out an interfacial polymerization reaction. After the reaction lasts for 30 seconds, remove the excess liquid. Then, soak the obtained membrane in the n-hexane solution for 10 seconds to remove the unreacted acyl chloride monomer. The reaction temperature is 25° C. and the reaction humidity is 60%.

[0089] Step 4: The microfiltration membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized traditional polyamide microfiltration membrane.

[0090] Comparative Example 2:

[0091] A method for preparing a conventional polyamide microfiltration membrane (no carbon nitride is added to the aqueous monomer solution, and both the wetting and interfacial polymerization reactions are carried out under light), comprising the following steps:

[0092] Step 1: Take piperazine as the aqueous phase monomer and trimesoyl chloride as the organic phase monomer, dissolve them in water and n-hexane respectively, and prepare a piperazine solution with a concentration of 4.0 mg / mL and a trimesoyl chloride solution with a concentration of 2 mg / mL respectively.

[0093] Step 2: Using polyethersulfone ultrafiltration membrane as the supporting base membrane and piperazine solution as the aqueous phase monomer, 5 ml of the solution was dripped onto the surface of the polyethersulfone supporting base membrane for aqueous phase infiltration. After standing for 120 seconds, the polyethersulfone filter membrane was taken out and the surface liquid was removed. The infiltration was carried out under light, and the light was formed by xenon lamp irradiation, and the intensity of the light was 100 mw / cm 2 .

[0094] Step 3: Immerse the surface of the ultrafiltration membrane in step (3) in a n-hexane solution of trimesoyl chloride to carry out an interfacial polymerization reaction. After the reaction lasts for 30 seconds, remove the excess liquid. Then, soak the membrane in the n-hexane solution for 10 seconds to remove the unreacted acyl chloride monomer. The reaction temperature is 25°C and the reaction humidity is 60%. The reaction is carried out under light, which is formed by xenon lamp irradiation, and the intensity of the light is 100mw / cm 2 .

[0095] Step 4: The microfiltration membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized traditional polyamide microfiltration membrane.

[0096] Comparative Example 3:

[0097] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride (carbon nitride is added to an aqueous monomer solution, but the wetting and interfacial polymerization reactions are not carried out under light), comprising the following steps:

[0098] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0099] Step 2: Prepare a 4 mg / mL piperazine aqueous solution, add carbon nitride membrane sol to make the concentration of carbon nitride in the piperazine aqueous solution 0.5 mg / mL, and disperse it evenly by ultrasonication to obtain a mixed dispersion; take 5 ml of the mixed dispersion and drop it onto the surface of the polyethersulfone support base membrane to soak for 120 seconds, and remove the residual liquid on the surface;

[0100] Step 3: Prepare a 2 mg / mL hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the hexane solution containing trimesoyl chloride for interfacial polymerization reaction. After the reaction lasts for 30 seconds, remove the excess liquid, and then soak the obtained membrane in the hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, and obtain a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C and the reaction humidity is 60%;

[0101] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0102] Comparative Example 4:

[0103] A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, comprising the following steps:

[0104] Step 1: Add 6g of melamine to a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, calcine for 4h, and then grind the calcined product into powder in a mortar to obtain a bulk carbon nitride powder. Place 1g of bulk carbon nitride powder in a beaker containing 20mL of concentrated hydrochloric acid, stir at 60℃ for 5h, then remove the concentrated hydrochloric acid by suction filtration, and wash the powder with deionized water until neutral. Dilute the filtered carbon nitride with deionized water, ultrasonicate for 2h, then centrifuge at 5000rpm for 20min, take the supernatant, and obtain a carbon nitride film sol with a concentration of 2.0mg / mL.

[0105] Step 2: Prepare a 4 mg / mL piperazine aqueous solution, add carbon nitride membrane sol to make the concentration of carbon nitride in the piperazine aqueous solution 1.0 mg / mL, and disperse it evenly by ultrasound to obtain a mixed dispersion; take 5 ml of the mixed dispersion and drop it onto the surface of the polyethersulfone support base membrane to soak for 120 seconds, and remove the residual liquid on the surface;

[0106] Step 3: Prepare a 2 mg / mL hexane solution of trimesoyl chloride, then immerse the surface of the ultrafiltration membrane in the hexane solution containing trimesoyl chloride for interfacial polymerization. After the reaction lasts for 30 seconds, remove the excess liquid. Then, soak the obtained membrane in the hexane solution for 10 seconds to remove the unreacted acyl chloride monomer, and obtain a high permeability membrane containing an ultrathin polyamide separation layer. The reaction temperature is 25°C and the reaction humidity is 60%;

[0107] Step 4: The high permeability membrane obtained in step 3 is placed in an oven for heat treatment at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane based on carbon nitride photogenerated positive charge regulation.

[0108] Application Example 1:

[0109] The multifunctional nanofiltration membranes prepared in Examples 1 to 4 were subjected to membrane flux tests. The separation performance of the obtained nanofiltration membranes was tested at 4 bar using cross-flow filtration with deionized water as the test liquid. The test liquid temperature was 25°C. After pre-pressing at 4 bar for 60 minutes, the produced water was collected for 30 minutes. The permeability of the nanofiltration membrane was calculated based on the volume of produced water per unit time. The results are shown in Figure 2 .

[0110] Comparative application example 1:

[0111] The multifunctional nanofiltration membranes prepared in Comparative Examples 1 to 4 were subjected to membrane flux tests. The separation performance of the obtained nanofiltration membranes was tested at 4 bar using cross-flow filtration and deionized water as the test liquid. The test liquid temperature was 25°C. After pre-pressing at 4 bar for 60 minutes, the produced water was collected for 30 minutes. The permeability of the nanofiltration membrane was calculated based on the volume of produced water per unit time. The results are shown in Figure 2 .

[0112] Application Example 2:

[0113] The multifunctional nanofiltration membrane prepared in Example 4 was used to perform membrane separation test on sodium sulfate aqueous solution. The separation performance of the obtained nanofiltration membrane was tested at 4 bar using cross-flow filtration method and 1 g / L sodium sulfate solution as the test liquid. The test liquid temperature was 25°C. After pre-pressurization at 4 bar for 60 minutes, the produced water was collected for 30 minutes. The desalination rate of the nanofiltration membrane was calculated based on the conductivity values ​​of the produced water and the influent water. The brine flux of the nanofiltration membrane was calculated based on the volume of produced water per unit time. The results are shown in Figure 3 .

[0114] Comparative application example 2:

[0115] The multifunctional nanofiltration membrane prepared in comparative example 2 was used to perform membrane separation test on sodium sulfate aqueous solution. The separation performance of the obtained nanofiltration membrane was tested at 4 bar using a cross-flow filtration method and a 1 g / L sodium sulfate solution as the test liquid. The test liquid temperature was 25°C. After pre-pressing at 4 bar for 60 minutes, the produced water was collected for 30 minutes. The desalination rate of the nanofiltration membrane was calculated based on the conductivity values ​​of the produced water and the influent water. The brine flux of the nanofiltration membrane was calculated based on the volume of produced water per unit time. The results are shown in Figure 4 .

[0116] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride, characterized in that: The steps include: (1) subjecting a nitrogen-containing precursor to thermal polymerization to obtain a bulk carbonitride compound, treating the bulk carbonitride compound in an acid solution to obtain a carbon nitride film-forming sol; adding the obtained carbon nitride film-forming sol to an aqueous solution of a polyamine monomer, and performing ultrasonic dispersion to obtain a mixed dispersion; (2) dissolving the organic phase monomer in an organic solvent and stirring to obtain an organic phase monomer solution; (3) adding the ultrafiltration support base membrane to the above-mentioned mixed dispersion to wet it, and then taking it out and adding it to the above-mentioned organic phase monomer solution to carry out interfacial polymerization reaction to obtain a high permeability membrane containing an ultrathin polyamide separation layer; wherein the wetting and interfacial polymerization reaction are both carried out under light; (4) After heat treatment of the high permeability membrane containing the ultra-thin polyamide separation layer, a nanofiltration membrane regulated by photogenerated positive charges of carbon nitride is obtained.

2. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (1), the nitrogen-containing precursor includes at least one of cyanamide, dicyandiamide, melamine, urea and thiourea.

3. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (1), the amount ratio of the bulk carbon nitrogen compound to the acid solution is 1 g: 10-50 mL; In step (1), the concentration of the obtained carbon nitride film-forming sol is 1.0 to 2.0 mg / ml; In step (1), the concentration of carbon nitride in the aqueous solution of the polyamine monomer is 0.1 to 2.0 mg / mL.

4. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (1), the polyamine monomer includes at least one of piperazine and its derivatives, o-phenylenediamine and its derivatives, m-phenylenediamine and its derivatives, diethylenetriamine, triethylenetetramine, polyethyleneimine, etc.

5. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (2), the organic phase monomer includes at least one of isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, cycloalkane polyacyl chloride, and polysulfonyl chloride; In step (2), the concentration of the organic phase monomer in the organic solvent is 0.5 to 3 mg / mL.

6. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (3), the illumination is provided by a xenon lamp; the intensity of the illumination is 100 to 300 mw / cm 2 .

7. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (3), the soaking time is 30 to 180 seconds.

8. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (3), the time of the interfacial polymerization reaction is 15 to 120 seconds, the temperature of the interfacial polymerization reaction is 20 to 30° C., and the humidity of the interfacial polymerization reaction is 45 to 70%.

9. The method for preparing a nanofiltration membrane according to claim 1, characterized in that: In step (4), the heat treatment temperature is 40 to 70° C. and the heat treatment time is 10 to 60 minutes.

10. The nanofiltration membrane prepared by the method for preparing a nanofiltration membrane by regulating interfacial polymerization reaction using photogenerated charges of carbon nitride as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon nitride modified Janus acid-resistant nanofiltration membrane as well as preparation method and application thereof

    CN112999870A

  • Carbon nitrogen compound-polyamide laminated nanofiltration membrane as well as preparation method and application thereof

    CN117225187A

  • High-filler three-layer structure functional composite film as well as preparation method and application thereof

    CN118085365A

Cited By

  • Visible light response carbon nitride / zinc oxide heterojunction modified reverse osmosis membrane and preparation method thereof

    CN121669018A

  • Visible light response carbon nitride / zinc oxide heterojunction modified reverse osmosis membrane and preparation method thereof

    CN121669018B